الذكاء الجسمي الحركي وعلاقته بالتصرف الخططي لدى لاعبي كرة القدم - بخدة, علي; لعريد, لحاج ((institut d’éducation sportive et physique / Université de Mostaganem, 2023, 2023)
هدف البحث إلى لإبراز العلاقة بين بين الذكاء الجسمي الحركي والتصرف الخططي لدى لاعبي كرة القدم، وكان الفرض من الدراسة أنه توجد علاقة ارتباطية بين التصرف الذكاء الجسمي الحركي والتصرف الخططي لدى لاعبي كرة القدم لفئة أقل من 19 سنة، تم الاعتماد في هذا البحث على المنهج الوصفي حيث اعتمد الطالبان على مقياسيالذكاء الجسمي الحركي و التصرف الخططي، وتكونت عينة البحث من 10 لاعبين لفريق النادي الرياضي لبلدية وادي الجمعة لفئة أقل من 19 سنة بولاية غيليزان، تم اختيارهم بطريقة عشوائية وبعد تحليل النتائج والمعالجة الإحصائية توصل الطالبان إلى ثبوت صحة فرضيات الدراسة التي نصت عن وجود علاقةارتباطيةبينالتصرفالذكاءالجسميالحركيوالتصرفالخططيلدىلاعبيكرةالقدملفئةأقلمن 19 سنة، و في الأخير يوصي الطالبان بضرورة الاعتماد على قياس الذكاء الجسمي الحركي في اختيار اللاعبين والعمل على تنميته. The objective of the research is to highlight the relationship between the physical-kinetic intelligence and the tactical behavior of football players, and the hypothesis of the study was that there is a correlation between the intelligence behavior physical-kinetic and tactical behavior of football players. for a category under 19 years old. In this research, we relied on the descriptive approach. Where both students relied on both measures of bodily-kinetic intelligence and tactical behavior, and the research sample consisted of 10 players for the sports club team. of the commune of oued djema for the category of less than 19 years in the wilaya of Gilizan, they were chosen at random, and after analysis of the results and statistical processing, the two students concluded that the validity of the hypotheses of the study which stipulated on the existence of a correlation between the behavior of physico-kinetic intelligence and the tactical behavior of footballers for a category of under 19 years, and finally the two students recommend the need to rely on the measurement of the physico-kinetic intelligence to choose players and work on its development
MES-2023-3
Keywords: الذكاء الجسمي الحركي - لتصرف الخططي - لاعبي كرة القدم / tactical behavior - Physical-kinetic intelligence - Football